Lynx lynx lynx (Linnaeus 1758 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Genes, 2018)
Lynx lynx (Linnaeus, 1758) —Eurasian Lynx Felis lynx Linnaeus, 1758 p.43; Type locality- Southern Sweden. Felis cervaria Temminck, 1827 p.106; Type locality- Northern Asia. Lynx lynx borealis : Kuroda in Uchida, 1927 p.37. L. borealis : Kishida & Mori, 1931 p.379. L. lynx cervaria : Won, 1958 p.442; Won, 1967 p.152. F. lynx cervaria : Kuroda, 1938 p.40; Won, 1968 p.320. F. lynx lynx : Yoon, 1992 p.113 L. lynx : Han, 1994 p.46; Won & Smith, 1999 p.20; Oh, 2004a p.154. Range: The distribution of the Eurasian lynx formerly covered the northwestern Korean Peninsula (Kim et al. 2015; Fig. 53). Only two lynx records from the 1910s at Guseong City, Pyeonganbuk Province and in the 1930s at Deokcheon City, Pyeongannam Province documented its presence in Korea (Won 1968). Recent records of lynx in North Korea are from Sinheung-gun and Baekam-gun in the 1990s (Kim et al. 2015). Unofficial records around the DMZ from South Korea cannot be validated (Yoo 2000). Historically, L. lynx has always been considered rare in Korea. Remarks: The populations in Korea were once regarded as L. l. cervaria (Won 1968), but this taxon remains uncertain since it became a synonym of L. l. lynx (Won & Smith 1999). Heptner and Sludskii (1972) recorded Lynx lynx stroganovi Heptner, 1969 in Manchuria close to Korea. Without any geographic barriers, L. l. cervaria from Korea and L. l. stroganovi from Machuria could be the same subspecies. Conservation status: The Red Data Book of North Korea lists the Eurasian lynx as a ‘Vulnerable’ species (MAB National Committee of DPR Korea 2002). The Ministry of Environment in South Korea designated L. lynx as an endangered species in 2005. Although the Eurasian lynx was reported only in extreme northern Korea, L. lynx was considered as ‘Regionally Extinct’ in South Korea and became a candidate for a ‘restoration project’ (NIBR 2012; Jo & Baccus 2016). Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, ...